Vitamin D receptor gene polymorphism as a factor of early osteopenia formation in case of a combined course of osteoarthritis and obesity in young people - Pasieshvili, Ludmila; Istomin, Andrii; Tereshkin, Konstantin; Tereshkinа, Olena (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2024)
Objective: to reveal the prognostic-diagnostic significance of polymorphism of vitamin D receptor (VDR) gene G63980A, reference SNP (rs) 1544410, and possible prognostication of the risk of disorders appearance in the structural-functional state of the bone tissue in a combined course of osteoarthritis (OA) and obesity in young people. Methods: the study group included 96 patients at the age of (35.5 ± 0.9) years with OA and obesity, the control group were 96 practically healthy people of the same age and gender, the comparison group consisted of 18 patients with OA and the normal body mass. Obesity was classified after calculation of the body mass (Ketle) index. The functional state of the locomotor system was assessed by the WOMAC scale. The mineral density of the bone tissue was measured with bone densitometer Explorer QDR W (Hologic). Gene polymorphism was investigated in the human genome by the method of polymerase chain reaction. Odds ratio (OR) of the disease development was calculated. Results: severe radiological stages of joints were revealed 2.4 times more frequently in OA combined with obesity than in isolated OA. Osteoporosis was diagnosed in 59.4 % of patients from the study group versus 50 % in the comparison one. In the study group, patients with polymorphic variants of VDR gene, who had the B allele, predominated. The following risk factors for the development of OA were revealed: bone fractures in patients and their family members in the past history, genotype variation in VDR gene, age of the onset of disease under 30 and the radiological stage of OA. Conclusions: clinical-instrumental manifestations of the disease worsen in young patients with OA against a background of obesity. The same patients form osteoporotic disorders as early as during five years of the combined course of the above nosologies. Prognostically unfavourable factors are as follows: the BB variant of VDR gene, fractures in patients and their family members’ past history, manifestation of the disease under 30 years of age and the radiological stage of OA.